Magnetic Resonance Q Mapping Reveals a Decrease in Microvessel Density in the arcAβ Mouse Model of Cerebral Amyloidosis - Ielacqua, Giovanna D.; Schlegel, Felix; Füchtemeier, Martina; Xandry, Jael; Rudin, Markus; Klohs, Jan (Frontiers in Aging Neuroscience, 2016)
Alterations in density and morphology of the cerebral microvasculature have been reported to occur in Alzheimer`s disease patients and animal models of the disease. In this study we compared magnetic resonance imaging (MRI) techniques for their utility to detect age-dependent changes of the cerebral vasculature in the arcAβ mouse model of cerebral amyloidosis. Dynamic susceptibility contrast (DSC)-MRI was performed by tracking the passage of a superparamagnetic iron oxide nanoparticle in the brain with dynamic gradient echo echo planar imaging. From this measurements relative cerebral blood volume (rCBV(DSC)) and relative cerebral blood flow (rCBF) were estimated. For the same animal maps of the relaxation shift index Q were computed from high resolution gradient echo and spin echo data that were acquired before and after superparamagnetic iron oxide nanoparticle injection. Q values were used to derive estimates of microvessel density. The change in the relaxation rates ΔR2* obtained from pre- and post-contrast gradient echo data was used for the alternative determination of rCBV (rCBV(ΔR2*)). Linear mixed effects modeling found no significant association between rCBV(DSC), rCBV(ΔR2*), rCBF and Q with genotype in 13-month old mice (compared to age-matched non-transgenic littermates) for any of the evaluated brain regions. In 24-month old mice there was a significant association for rCBV(DSC) with genotype in the cerebral cortex, and for rCBV(ΔR2*) in the cerebral cortex and cerebellum. For rCBF there was a significant association in the cerebellum but not in other brain regions. Q values in the olfactory bulb, cerebral cortex, striatum, hippocampus, and cerebellum in 24-month old mice were significantly associated with genotype. In those regions Q values were reduced between 11-26 % in arcAβ mice compared to age-matched non-transgenic littermates. Vessel staining with CD31 immunohistochemistry confirmed a reduction of microvessel density in the old arcAβ mice. We further demonstrated a region-specific association between parenchymal and vascular deposition of β-amyloid and decreased vascular density, without a correlation with the amount of Aβ deposition. We found that Q mapping was more suitable than the hemodynamic read-outs to detect amyloid-related degeneration of the cerebral microvasculature.